2021
DOI: 10.17516/1997-1370-0825
|View full text |Cite
|
Sign up to set email alerts
|

Pedagogical Senses of Digital Learning ion the Context of the Covid‑19 Pandemic: Case Studies of Several Eastern European Countries

Abstract: In the context of the Covid‑19 pandemic, teacher education at universities has faced great problems concerning the teaching-learning practice. Educational processes have become possible only with the help of digital technologies. The development of digital technologies and the new level of accessibility to educational resources have opened up new ways for teaching and learning and the creation of new didactic scenarios. The reopening of educational institutions after the Covid‑19 is followed by many tasks that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Earlier findings showed that absolute control over children's internet use or extremely strong restrictions do not foster children's digital skills, which, in turn, lowers their potential for professional development [13]. We believe that the COVID−19 pandemic from 2020-2022, which caused a shift to distance learning, accelerated the digitalization of modern life [58][59][60], so this is probably why a certain number of parents have decreased the level of their digital control and increased their support.…”
Section: Groups Of Children Whose Parents Demonstrate Different Media...mentioning
confidence: 91%
“…Earlier findings showed that absolute control over children's internet use or extremely strong restrictions do not foster children's digital skills, which, in turn, lowers their potential for professional development [13]. We believe that the COVID−19 pandemic from 2020-2022, which caused a shift to distance learning, accelerated the digitalization of modern life [58][59][60], so this is probably why a certain number of parents have decreased the level of their digital control and increased their support.…”
Section: Groups Of Children Whose Parents Demonstrate Different Media...mentioning
confidence: 91%
“…Недавний беспрецедентный случай длительной социальной изоляции в связи с пандемией COVID-19 повлиял практически на все сферы жизни современных семей с детьми (Koinova-Zoellner et al, 2021;Первичко и др., 2022). С целью снижения кривой новых случаев заболевания коронавирусом во всем мире были введены строгие ограничения на перемещение граждан и посещение общественных мест.…”
Section: социальная изоляция как фактор риска для развития рабочей па...unclassified
“…The researchers argue that the greatest barriers to the integration of digital technologies in the educational process include low digital competence of teachers, their unpreparedness to work in the digital format with the use of distance or mixed learning technologies [11], "absence of technical and pedagogical skills on their part, necessary to integrate digital facilities into learning" [3, p. 9], haphazard application of digital technologies in class, related unconscious estranged perception of modern digital transformations in the educational policy [12]. It can be considered that developed digital skills represent a prerequisite for appropriate and practicable use of digital technologies in pedagogical activities.…”
Section: Review Of Sourcesmentioning
confidence: 99%